The Impact of IT Leadership on Organizational Change Management, IT Business Alignment, and IT Business Value: A Study of Food Processing Manufacturing Companies in East Java in 2025 - Amma, Fazizah; Sabaruddin, .; M., Sulhan; Eko Agus, Alfianto (INTI International University, 2026)
IT-Business Alignment and IT-Business Value are vital for the effective implementation of information technology, especially in large-scale food processing manufacturing. Misalignment between IT and business strategies can have long-term negative effects. IT Leadership, particularly from the Chief Information Officer (CIO), plays a decisive role in achieving alignment, delivering business value, and managing organizational change. This study examines the rel Faculty of Social and Political Sciences, Yudharta University Pasuruanationships among four variables: IT Leadership, Organizational Change Management, IT-Business Alignment, and IT-Business Value This study employs the Structural Equation Modeling (SEM), method based on Partial Least Squares (PLS) using SmartPLS software to analyze the relationships among latent variables. This method was chosen for its ability to simultaneously assess measurement and structural models and its suitability for medium-sized samples with non-normal data distribution.The population of this study consists of 377 food processing manufacturing companies large scale industry in East Java, with a sample size of 194 respondents. The sampling technique employed was purposive sampling from the total population of 377 companies, covering five Regional Coordination Agency (Bakorwil) areas: Madiun, Bojonegoro, Malang, Pamekasan, and Jember. The findings of this study indicate significant relationships among the variables as follows: 1) IT Leadership has a significant effect on Organizational Change Management. 2) IT Leadership has a significant effect on IT-Business Alignment. 3) Organizational Change Management has a significant effect on IT-Business Alignment. 4) Organizational Change Management has a significant effect on IT-Business Value. 5) IT-Business Alignment has a significant effect on IT-Business Value. This study found that IT leadership drives organizational change management and IT-business alignment, which in turn enhances IT business value through efficiency, innovation, and the competitiveness of food processing manufacturing companies in East Java. The novelty of this study lies in its integrated examination of the influence of IT Leadership, Organizational Change Management, IT-Business Alignment, and IT-Business Value in the food processing manufacturing industry across five Bakorwil regions in East Java, a topic rarely addressed previously, thus providing contextual insights for IT strategy in the sector.